THE IMPACT OF 4Ps MARKETING MIX ELEMENTS ON PURCHASE INTENTION AND LOYALTY (STUDY OF HEALTHY CATERING BUSINESS) (The Indonesian Journal of Business Administration, 2019)
Increasing healthy lifestyle, the need to eat healthy food also increases. The increasing for healthy food makes opportunities for healthy catering businesses. Fitmeal_id is one of the new healthy catering. Fitmeal_id has not implemented the right marketing mix. To maximize the marketing mix concept, the focus of this research is impact of elements of  the marketing mix 4Ps on purchase intention and loyalty in a healthy catering business. The method of the research is using quantitative and qualitative method. After the data collected, testing of the survey results carried out by using several SPSS tests. There are Validation Test and Reliability Test those include in Instrumentation test, Normality (Graphic Analysis and Kolmogorov-Smirnov), Heteroscedasticity, Multicollinearity those include in Classic Assumption Test, T-test and Path Analysis those include in Hypothesis Test, and Determination Coefficient.The results of this study involved 150 respondents. Tests conducted on the results of the questionnaire showed the influence of the dependent variable on the independent variable, on all three models. Based on path analysis the biggest effect of 4Ps Marketing Mix on purchase intention is the promotion variable. Based on path analysis the biggest effect of 4Ps Marketing Mix on loyalty is the promotion variable. The coefficient of determination or R Square purchase intention on loyalty is 0,753 which means 75,3% of dependent variable loyalty explained by the independent variable Purchase Intention.Keyword: 4Ps, Loyalty, Marketing Mix, Purchase Intention, and Validation Test